Comparison of Resistance Symbols in Poems of Kaiser Aminpoor and Ayyed Hassan Hosseini with Poems of Ali Ahmad Sa'id and Jabra Ibrahim Jabra (Adonis) - Alizadeh, Amir Haj; Moghadam, Seyyed Mohammad Alavi; Radfar, Abolghassem (Journal of History Culture and Art Research, 2017)
The resistance poets provide exquisite images of natural phenomena, personalities, and religious, historical, mythological, epic and national events. Selection and usage of these images as symbols of resistance in the poems depict the mood of fight as well as the other concepts to the reader. By implementing a comparative study on the resistance symbols in the poems discussed in this study. This article shows that natural symbols have high frequency and the similarity of the symbols in each of four categories (natural, religious, historical, epic and other symbols) are very low because of differences in ideas. Examining the content of the heavily used symbols by Arab poets suggest that they discourse to consciousness of the Arab nation. However, in the case of Iranian poets, they try to strengthen the spirit of struggle and resistance against a hostile force. The most important feature of the symbols of Arab poets is the use of self-made and private symbols to a very high extent, and this can be seen in the poets in Iran very low. Arab poets, in orientation to the West, have used in a large amount of mythological symbols outside their territory, especially Greece and Egypt that don’t appear in Iranian poets.